Speaking with the Dead - Tomlinson, Matt (punctum books, 2026)
If you tried speaking with a dead person and they gave you a clear response, how would you react? Mediums develop their minds and bodies to communicate messages from the deceased to their living loved ones, and in Speaking with the Dead, anthropologist Matt Tomlinson describes his experiences training as a medium with a Spiritualist congregation in Canberra, Australia. The book is written in a first-person narrative style that brings “extrahuman” relationships to life, showing what it is like to learn and practice mediumship: the strategic suspension of skepticism; the wobbly first attempts; the embarrassing failures; and the moments, both unsettling and enthralling, when someone tells you that yes indeed, you’ve just described her grandfather who died in 1978. Speaking with the Dead brims with stories of talented mediums and Tomlinson is not interested in proving or disproving mediumship, preferring instead to illustrate how mediums bring their practices to life. In contrast to the popular image of mediums as shameless frauds, Tomlinson describes earnest and committed seekers from a wide range of backgrounds who often struggle to understand their own experiences. Their profits are therapeutic rather than financial. And they worry about endings as much as anyone else: the passing of physical lives, the closure of beloved churches. Speaking with the Dead is ultimately a book about the lively side of death, grounded in Spiritualists’ conviction that life is eternal and your social network extends to the astral plane. It is a close examination of how mediumship works culturally, which is to say, how mediums and audiences work together to create senses of transcendent connection.